The survey of possibility of beluga (Huso huso) sturgeon culture in different densities in Khuzestan province - Yooneszadeh Feshalami, Mohammad; Mortezavizadeh, S.A.; Eskandari, Gh.R.; Amiri, F.; Bosak Kahkesh, F.; Nikpey, M.; Sabz Alizadeh, S.; Eydizadeh, M.R.; Gholampor, K. (Iranian Fisheries Science Research Institute, 2016)
The influence of stocking density was investigated on growth, survival and FCR of great sturgeon (Huso huso) juvenile in north of Khuzestan province (Dezful). The study was conducted by Southern Iran Aquaculture research center. This study was done from September 2013 to July 2014 in three stage with different weight of Huso huso juveniles. In the first stage density of 1.5, 3 and 6 kg/m^2 during two month was performed. The initial weight and length of fish in this stage considered as 143±0.29 g and 316±1.1 mm. In the second stage 3, 6 and 9 kg/m2 density were introduced. The initial weight and length of fish in this stage considered as 548.58±33.26 g and 416.5±0.81 mm and duration of the stage was 84 days. In the third stage 6, 9 and 12 kg/m^2 density were introduced and initial weight and length were 1571.33±71.33 g and 687.5±10.96 mm. Growth and feeding index were assess in each stage. In the first stage monthly blood samples were collected from each density. In this stage bold and hormonal indices were assessed. The results showed that the average final weight in stage 1 in 1.5, 3 and 6 kg/m^2 densities were 527.27±6.82 g, 467.91±18.81 g and 431.02±24.25 g respectively. The highest average of weight was in treatment 1 and it has significant difference with treatment 3 (P<0.05). FCR was lower than 0.7 in every treatment. FCR, condition factor, daily growth, special growth index, BWI and food performance index have not significant difference in treatments. In the second stage, average final weight of Huso huso was 1734.91±97.65g, 1525.88±57.20 g and 1370.95±1593 g respectively. The highest average weight was in treatment 1 and has significant difference with treatment 2 (P<0.05) FCR in treatment 1, 2 and 3 were 0.92±0.2, 0.96±0.26 and 1.11±0.36 respectively and there is no significant difference between them (P>0.05). FCR, condition factor, daily growth, special growth index, BWI and food performance index have not significant difference in treatments. Daily growth rate in treatment 1, 2 and 3 were 13.93±2.83, 11.44±2.65 and 9.6±2.49 respectively. In the third stage the average final weight in 6, 9 and 12 kg/m^2 densities were 3232.22±66.12g, 3407.39±119.73g and 2869.72±135.7g. The highest average weight was in treatment 2 and has significant difference with treatment 3 (P<0.05). FCR in treatment 1, 2 and 3 were 1.19±0.2, 1.25±0.1 and 1.45±0.27 respectively and there is no significant difference between them (P>0.05). FCR, condition factor, daily growth, special growth index, BWI and food performance index have not significant difference in treatments. Daily growth rate in treatment 1, 2 and 3 were 20.37±3.12 g/day, 19.90±4.2 g/day and 16.36±3.64 g/day respectively.